Cultural Representations of Borderline Personality Disorder - Munson, Katherine A.; Janney, Carol A.; Goodwin, Kelsie; Nagalla, Madhavi (Frontiers in Sociology, 2022)
Background/Objective: The objective of this systematic review was to compare methods of self-harm and psychological stressors in Borderline Personality Disorder (BPD) across different cultures. Methods: An extensive database search was conducted along with manual searches and reference/citation searches. A total of 21 articles were reviewed from several Eastern and Western nations. Results: Key differences were noted in the methods of self-harm. Eastern nations reported higher rates of self-poisoning whereas Western nations reported higher rates of skin-mutilating behavior. Conclusions: Additional research should be conducted into the presentation of BPD in different cultures. An improved understanding of the cultural presentations of BPD could improve diagnosis and treatment in various populations.